Fenomena Self-Alienation: Pengalaman Mahasiswa Perantauan dalam Mengelola Konflik Nilai dan Kehilangan Diri Otentik di Yogyakarta - Dewi Setyowati (Lembaga Pengembangan Kinerja Dosen, 2026)
Higher education often marks an important stage in which individuals migrate to pursue independence and prepare for their future careers. However, relocating to a new environment, particularly Yogyakarta as a multicultural city known as